2019
DOI: 10.1002/ece3.4842
|View full text |Cite
|
Sign up to set email alerts
|

Studying the microbiota of bats: Accuracy of direct and indirect samplings

Abstract: Given the recurrent bat‐associated disease outbreaks in humans and recent advances in metagenomics sequencing, the microbiota of bats is increasingly being studied. However, obtaining biological samples directly from wild individuals may represent a challenge, and thus, indirect passive sampling (without capturing bats) is sometimes used as an alternative. Currently, it is not known whether the bacterial community assessed using this approach provides an accurate representation of the bat microbiota. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Despite these cohort-level differences, several dominant bacterial families in both cohorts, including Enterobacteriaceae, Moraxellaceae, and Streptococcaceae, comprise the microbiota of wild rousette and pteropid bats [51][52][53][54] , potentially signaling a pattern of dominance of a few families across multiple bat species. Several of these families, including Enterobacteriaceae and Moraxellaceae, belong to the Pseudomonadota phylum (renamed from Proteobacteria in 2021), the abundance of which may indicate microbial dysbiosis in humans 20,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these cohort-level differences, several dominant bacterial families in both cohorts, including Enterobacteriaceae, Moraxellaceae, and Streptococcaceae, comprise the microbiota of wild rousette and pteropid bats [51][52][53][54] , potentially signaling a pattern of dominance of a few families across multiple bat species. Several of these families, including Enterobacteriaceae and Moraxellaceae, belong to the Pseudomonadota phylum (renamed from Proteobacteria in 2021), the abundance of which may indicate microbial dysbiosis in humans 20,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the difficulty to obtain samples directly from wild individuals, a comparison between directly and indirectly collected samples was made to determine whether indirect sampling would produce results similar to direct sampling ( Dietrich and Markotter, 2019 ). The results obtained showed that even if the sampling approach influenced the microbiota composition – i.e.…”
Section: Bacteriamentioning
confidence: 99%
“…The results obtained showed that even if the sampling approach influenced the microbiota composition – i.e. cross-contamination in both methods or temporal sampling – niche specialization among excreta was well assessed by both methods ( Dietrich and Markotter, 2019 ). Furthermore, significant differences in alpha-diversity microbial composition between small and large intestine and feces samples was observed in two insectivorous species supporting that fecal samples cannot be used as microbial inventories in other gut regions ( Wu et al, 2019 ).…”
Section: Bacteriamentioning
confidence: 99%
“…Bats ( Chiroptera ) are a diverse group of mammals with more than 1400 different species with abilities to inhabit various ecological niches and environments (Winter et al 2016 ; Gorbunova et al 2020 ). Although bats are geographically widespread, the ecology of their microbial communities and the role involved in bat health and behavior are scarce, especially on the microbiota residing in bat’s excreta accumulated in the form of guano, which could be potentially involved in pathogen transmission to humans (Dietrich et al 2018 ; Dietrich and Markotter 2019 ). Bats revealed versatile feeding behavior; they have a flying capacity and inherent characteristics which makes them as highly potent vectors and natural reservoir hosts for many pathogens.…”
Section: Introductionmentioning
confidence: 99%